Healthcare providers’ perceptions and understanding of voluntary medical male circumcision in KwaZulu-Natal, South Africa: A qualitative study - Celenkosini T. Nxumalo; Gugu G. Mchunu (South African Family Practice)
Background: There is compelling evidence that voluntary medical male circumcision (VMMC) reduces the chances of heterosexual transmission of HIV infection. Healthcare workers are among the key influencers in terms of the scale-up of VMMC as they are often involved in mobilisation for uptake. There is a paucity of qualitative research on healthcare workers’ experiences, understanding and perceptions of VMMC; particularly in the South African rural primary healthcare context. This study was conducted to examine healthcare workers perceptions and understanding of VMMC in KwaZulu-Natal, South Africa.